Thermal comfort as assumption for architectonic landscape design: the case of outdoor spaces of the Petrobras New Research Center in Rio de Janeiro, CENPES II - Monteiro, Leonardo Marques (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper presents the outdoor thermal comfort study for the Petrobras New Research Centre, in Rio de Janeiro, CENPES II, which was part of a bigger research and consultancy project involving environmental and architectural issues. The architectural design was the subject of a national competition, encompassing ten types of buildings, which represented the expansion of the existing research centre, CENPES I, dating from 1970s. Open spaces were incorporated in the proposal as places for long permanence, raising the importance of the interaction between architecture and climate. The diversity of architectural and landscape solutions created a variety of open spaces where thermal comfort needed to be verified. The methods were based on Outdoor Neutral Temperature and New Effective Temperature for the application of an adaptive model. Ventilation and especially shadows proved to be absolutely necessary. Overall, the open spaces studied showed satisfactory thermal comfort, especially due to the consideration of ventilation and shading strategies in the design of the open spaces and the buildings.